KEKAL: Digital Creative Comics as an Innovative Media in Dance Learning to Enhance Students' Creativity in Elementary School - Fathia Rosyida Wijaya; Deasylina da Ary (Universitas Negeri Malang, 2025)
Abstract: The purpose of this development is to develop KEKAL media: Digital Creative Comic through the folklore “The Dragon Snake has many friends” to improve students' creativity by knowing its feasibility and effectiveness. This research uses a type of R&D (Research & Development) research with the ADDIE development model: Analysis, Design, Develop, Implement, & Evaluation. This study used a small scale with 6 students and a large scale with 20 students in class III SDN Sadeng 02. The data collected were observation, interview, questionnaire, posttest-pretest, and documentation. Based on the results of expert validation, this media is considered effective and feasible, with a score of 92 percent from material experts, 86 percent from media experts, 96 percent from teachers, and 94 percent from students. The results of this study indicate that KEKAL learning media Digital Creative Comic Media is proven to be effective and feasible to use in learning Dance Art in class III SDN Sadeng 02 Semarang City, with the results of Normality Test greater than 0.05, T-test smaller than 0.05 and N-Gain Test of 0.74 which shows high effectiveness in improving student creativity.Abstrak: Tujuan dari pengembangan ini adalah untuk mengembangkan media KEKAL: Komik Kreatif Digital melalui folklore